The Dual Role of Career Women within the Family: An Islamic Legal Perspective on Female Civil Servants in Indonesia - Desi, Desi Noviliani; Fadzlurrahman, Fadzlurrahman (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2025)
Problem statement: The transformation of women’s roles, particularly those of wives who work as civil servants (ASN), reflects the evolving social dynamics and new challenges present in contemporary society. Objective: This study aims to analyse the dual roles of ASN wives from the perspective of Islamic law, with a focus on the balance between professional and domestic responsibilities. Methods: A qualitative approach is employed, utilising a literature review and in-depth interviews with ASN wives selected through the ASN women’s organisation network. Results: The findings indicate that the majority of ASN wives work to support the family economy and receive backing from their husbands. Islamic principles permit women to pursue careers, provided they fulfil their household duties and adhere to Islamic tenets. The primary challenges encountered include psychological pressure, time management, and social expectations; however, these obstacles can be mitigated through open communication, equitable task distribution, and familial support. Conclusion: This research underscores the necessity for inclusive policies and a contextual understanding of Islamic law in addressing the dual roles of women within both the household and society.